53 The positive impact of COVID-19 on undergraduate conferences: inclusion beyond our borders. (23rd February 2023) - Padhiar, Asha; Morrish, Samuel; Willock, Marissa; Wheeler, Olivia; Brown, Shereen; Poisson, Jeroen; Miller-Maclean, Rhian; Sarraf-Yazdi, Reza; Smith, Jonathan; Blackburn, Simon; Costa, Cristine Sortica da
Abstract : Background: The way we deliver undergraduate education has changed during the pandemic. Great Ormond Street Hospital Summer School (GSS) is an annual conference that aims to encourage medical students to consider a career in Paediatrics. Since 2020, the GSS has been delivered virtually, becoming accessible for students from the UK and abroad. Aims: We analysed the impact of changing the GSS from fully in person to online and hybrid formats on participation, comparing the data from the last four conferences. Results: (See figure 1 ). Discussion: The Covid-19 pandemic encouraged us to think creatively on how we can still provide a high-quality educational experience using online technology. Students from different areas of the UK and abroad joined the GSS without incurring travel and accommodation costs. A significant increase in the percentage of international students was observed in 2021, which demonstrates the interest from those outside the UK. With the development of online fatigue and the slow return of clinical placements, we observed a decrease in the number of registrations in 2021 and 2022 compared to 2020. However, the percentage of international students remained above 20%. The conference gave us the opportunity to inspire, educate and share the innovative work we do at GOSH with a much wider audience. Students described their experiences as insightful and inspiring. With the easing of restrictions in 2022, we designed a hybrid conference, involving 2 online days and 1 day with in person workshops. Our challenge now is to continue engaging with students from inside and outside the UK and bring innovative ways to deliver our online conference